“Candidatus Chlorobium masyuteum,” a Novel Photoferrotrophic Green Sulfur Bacterium Enriched From a Ferruginous Meromictic Lake - Lambrecht, Nicholas; Stevenson, Zackry; Sheik, Cody S.; Pronschinske, Matthew A.; Tong, Hui; Swanner, Elizabeth D. (Frontiers in Microbiology, 2021)
Anoxygenic phototrophic bacteria can be important primary producers in some meromictic lakes. Green sulfur bacteria (GSB) have been detected in ferruginous lakes, with some evidence that they are photosynthesizing using Fe(II) as an electron donor (i.e. photoferrotrophy). However, some photoferrotrophic GSB can also utilize reduced sulfur compounds, complicating the interpretation of Fe-dependent photosynthetic primary productivity. An enrichment (BLA1) from meromictic ferruginous Brownie Lake, Minnesota, USA contains an Fe(II)-oxidizing GSB and a metabolically flexible putative Fe(III)-reducing anaerobe. ‘Candidatus Chlorobium masyuteum’ grows photoautotrophically with Fe(II) and possesses the putative Fe(II) oxidase-encoding cyc2 gene also known from oxygen-dependent Fe(II)-oxidizing bacteria. It lacks genes for oxidation of reduced sulfur compounds. Its genome encodes for hydrogenases and a reverse TCA cycle that may allow it to utilize H2 and acetate as electron donors, an inference supported by the abundance of this organism when the enrichment was supplied these substrates and light. The anaerobe ‘Candidatus Pseudopelobacter ferreus’ is in low abundance (~1%) in BLA1, and is a putative Fe(III)-reducing bacterium from the Geobacterales ord. nov. While ‘Ca. C. masyuteum’ is closely related to the photoferrotrophs C. ferroooxidans strain KoFox and C. phaeoferrooxidans strain KB01, it is unique at the genomic level. The main light-harvesting molecule was identified as bacteriochlorophyll c with accessory carotenoids of the chlorobactene series. BLA1 optimally oxidizes Fe(II) at a pH of 6.8, and the rate of Fe(II) oxidation was 0.63 ± 0.069 mmol day-1, comparable to other photoferrotrophic GSB cultures or enrichments. Investigation of BLA1 expands the genetic basis for phototrophic Fe(II) oxidation by GSB and highlights the role these organisms may play in Fe(II) oxidation and carbon cycling in ferruginous lakes.